Plant penetration activities by the flatid planthopper Metcalfa pruinosa (Hemiptera: Fulgoroidea): an electrical penetration graph‐histology analysis. (13th February 2016) - Seo, B. Y.; Jung, J. K.; Park, C.‐G.; Lee, S.‐G.; Park, Y.‐L.
Abstract: The citrus flatid planthopper, Metcalfa pruinosa Say (Hemiptera: Flatidae), is a very polyphagous native insect in North America and currently a serious pest in Europe and South Korea. To understand the feeding behaviour of M. pruinosa, stylet penetration behaviour of M. pruinosa was investigated with an electrical penetration graph (EPG) system. This study reports seven EPG waveforms related to M. pruinosa feeding behaviour: np (no stylet penetration), Mp1 (initiation of stylet penetration), Mp2 (stylet movement and salivation), Mp4 (phloem feeding), Mp4‐H (honeydew excretion), Mp5 (xylem feeding) and Mp6 (unknown). To determine respective feeding behaviour related to the Mp4 and Mp5 waveforms, stylets were cut with a laser beam, and the location of the stylet tip within plant tissue was examined. We found plant sap was exuded from the severed stylets only when the Mp4 waveform was observed, suggesting phloem sap ingestion. The stylet tip was located in the xylem region, indicating xylem‐feeding activity, when the Mp5 waveform was observed. The analysis of 24 different EPG parameters suggests that M. pruinosa stylets reached the vascular bundle of a plant within ca. 5 min and spend ca. 70% of the time feeding on xylem and phloem feeding. This is the first study that reports seven distinctive EPG waveforms with respect to the feeding behaviour of M. pruinosa which could help determine host specificity and host plant susceptibility.